Familial Longevity Is Not Associated with Major Differences in the Hypothalamic–Pituitary–Gonadal Axis in Healthy Middle-Aged Men - van der Spoel, Evie; Roelfsema, Ferdinand; Jansen, Steffy W.; Akintola, Abimbola A.; Ballieux, Bart E.; Cobbaert, Christa M.; Blauw, Gerard J.; Slagboom, P. Eline; Westendorp, Rudi G. J.; Pijl, Hanno; van Heemst, Diana (Frontiers in Endocrinology, 2016)
Context: A trade-off between fertility and longevity possibly exists. The association of the male hypothalamic-pituitary-gonadal (HPG) axis with familial longevity has not yet been investigated. Objective: To study 24h hormone concentration profiles of the HPG axis in men enriched for familial longevity and controls. Design: We frequently sampled blood over 24 hours in 10 healthy middle-aged male offspring of nonagenarian participants from the Leiden Longevity Study together with 10 male age-matched controls. Individual 24h luteinizing hormone (LH) and testosterone concentration profiles were analysed by deconvolution analyses to estimate secretion parameters. Furthermore, the temporal relationship between LH and testosterone was assessed by cross-correlation analysis. We used (cross-) approximate entropy to quantify the strength of feedback and/or feedforward control of LH and testosterone secretion. Results: Mean (95% confidence interval (CI)) total LH secretion of the offspring was 212 (156–268) U/L/24h, which did not differ significantly (p=0.51) from the total LH secretion of controls (186 (130–242) U/L/24h). Likewise, mean (95% CI) total testosterone secretion of the offspring (806 (671–941) nmol/L/24h) and controls (811 (676–947) nmol/L/24h) were similar (p=0.95). Other parameters of LH and testosterone secretion were also not significantly different between offspring and controls. The temporal relationship between LH and testosterone and the strength of feedforward/feedback regulation within the HPG axis were similar between offspring of long-lived families and controls. Conclusions: This relatively small study suggests that in healthy male middle-aged participants, familial longevity is not associated with major differences in the HPG axis. Selection on both fertility and health may in part explain for the results.